What it means to succeed: personal conceptions of career success held by male and female managers at different ages - Sturges, Jane (Cranfield University, 1996)
The aim of this research is to investigate how managers define career success for themselves. It seeks to discover what differences there are in the way that women and men, and older and younger managers, see their own career success. It fills an identifiable gap in the literature on career success, in that it examines the subject from the point of view of the individual, not the organisation. In doing so, it responds to calls for work in this area, especially the development of "orientational categories" which classify peoples' attitudes to careers according to their individual predispositions (Bailyn 1989). The research, which took place in BT, uses qualitative methods, in particular in-depth interviewing, to elicit managers' own definitions of career success. Using techniques of qualitative data analysis and with the help of NUD. IST computer software, it develops a typology of managerial career success, which shows that managers view their own career success in one of four ways: as a Climber, who emphasises hierarchical position, pay and enjoyment in their definition of success; as an Expert, who sees success as being good at what they do and getting personal recognition for this; as an Influencer, who defines career success primarily as organisational influence; and as a Self-Realiser, who judges their own career success by achievement at a very personal level. Women managers, who generally base their definitions of career success on internal and intangible criteria, are more likely to be Experts and Self-Realisers; men, who tend to base their ideas of success on external criteria are more likely to be Climbers and Influencers. Younger managers, especially men, are most likely to be Climbers, and older managers, Influencers who often see their own success in terms of achieving something at work by which they will be remembered.